2013
DOI: 10.1186/1475-9276-12-95
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and healthcare-seeking among women with low educational attainment: analysis of cross-sectional data from the 2011 Nepal demographic and health survey

Abstract: IntroductionResearch suggests that literacy plays a key role in mediating the relationship between formal education and care-seeking among women in developing countries. However, little research has examined literacy’s role independently from formal education. This differentiation is important, as literacy programs and formal schooling entail distinct intervention designs and resources, and may target different groups. To assess the relationship between literacy and healthcare-seeking among Nepali women of low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 24 publications
5
16
1
Order By: Relevance
“…This finding could also be attributed to low skilled delivery in the communities because most of the peoples who are Muslims according to them do not allow their wives to deliver in the hospital or go for antenatal care in any health facility. This finding is in agreement with studies conducted in Ghana which indicated that 66.3% of mothers who were Muslim faithful and a majority showed a preference for TBA (96%) [46]. This preference was also indicated by respondents in the focus group discussions.…”
Section: Discussionsupporting
confidence: 91%
“…This finding could also be attributed to low skilled delivery in the communities because most of the peoples who are Muslims according to them do not allow their wives to deliver in the hospital or go for antenatal care in any health facility. This finding is in agreement with studies conducted in Ghana which indicated that 66.3% of mothers who were Muslim faithful and a majority showed a preference for TBA (96%) [46]. This preference was also indicated by respondents in the focus group discussions.…”
Section: Discussionsupporting
confidence: 91%
“…A similar positive association of women's level of education and four or more ANC visits was observed in the studies that analyzed the Ethiopian Demographic and Health Survey (EDHS) [28], and Bangladesh Demographic and Health Survey (BDHS) [25]. This may be due to better health-seeking behavior of women who had higher educational attainment [29][30][31].…”
Section: Number Of Anc Visitssupporting
confidence: 57%
“…Awareness of cervical cancer was positively associated with having knowledge of STIs, any formal education, current contraception use, and previously having had an abortion in our study population. Given that knowledge of STIs and formal education are both associated with health literacy (Dimmitt et al, 2013;Lam et al, 2013;Wang et al, 2014) and that both contraception use and abortion are indicative of accessing medical care, it is possible that women who are accessing health care for reproductive issues unrelated to cervical cancer are learning about cervical cancer through their doctors. Previous studies conducted in developing countries suggest that women who sought treatment of gynecological problems had higher levels of cervical cancer awareness, possibly indicating that knowledge of cervical cancer was transferred from doctor to patient during clinical visits (Dhamija et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the use and efficacy of the HPV vaccine in developing countries have suggested that vaccine distribution could be an effective way to mitigate cervical cancer in low-and middle-income countries (Fesenfeld et al, 2013;Termrungruanglert et al, 2012). Demonstration projects in Peru, India, Uganda, and Vietnam have shown high levels of vaccination coverage using schoolbased programs targeting teen girls (LaMontagne et al, 2011). While effective rollout of the HPV vaccine has been shown to be possible in low-income countries, disseminating knowledge of HPV and cervical cancer remains challenging.…”
Section: Introductionmentioning
confidence: 99%